El principio trascendental de la razón y la necesidad de la naturaleza en el Apéndice de la Dialéctica trascendental - Rodríguez Hernández, Montserrat (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This paper presents an original proposal regarding what, in the secondary literature, has been called The Necessitation Account. This theory, on the one hand, defends the necessity of the particular laws of nature based on a metaphysical consideration that holds that the laws are derived from the natures of things; on the other hand, it maintains that the necessity of the particular laws is not knowable by human beings. In this paper, I argue that the latter claim is unsatisfactory and propose to amend the epistemic thesis, pointing out that through the transcendental principle of reason we can understand the metaphysical groundings of nature, and I propose a solution to a skeptical problem that has not been addressed by the defenders of this theory regarding systematic unity and classifications of nature.
Keywords: nature; laws of nature; necessity; the Necessitation Account; the transcendental principle of reason